Implementation strategies for occupational therapists to advance goal setting and goal management - Kang, Eunyoung; Chen, Julie; Foster, Erin R. (Frontiers in Health Services, 2023)
Background There is a need for an effective evidence-based system to support high-quality goal setting and goal management implementation. We developed a new system for community-based rehabilitation, MyGoals, along with implementation strategies to support occupational therapists (OTs) in its administration. This study evaluates the acceptability, appropriateness, and feasibility of the implementation strategies, Clinician Education and Audit & Feedback. It also explores whether OTs achieve the change objectives of the MyGoals implementation strategies and MyGoals intervention fidelity. Methods This mixed-methods case series study evaluated the MyGoals implementation strategies developed using Implementation Mapping (IM), specifically IM Task 5 – Implementation Outcome Evaluation. Seven OTs and 13 adults with chronic conditions participated in this study. OTs participated in two Clinician Education sessions, delivered two MyGoals interventions, and participated in two Audit & Feedback sessions. We evaluated the implementation strategies using the Acceptability of Intervention Measure (AIM), Intervention Appropriateness Measure (IAM), Feasibility of Intervention Measure (FIM), and semi-structured interviews and explored the OTs' self-rated MyGoals change objectives achievement and the intervention fidelity using quantitative MyGoals intervention fidelity measures and interviews. Quantitative data were analyzed using descriptive statistics. Qualitative data were analyzed by two independent coders using content analysis. Results Seven OTs participated in this study (mean years of professional experience = 9.3, SD = 5.9). Clinician Education and Audit & Feedback had high AIM (M = 17.9, SD = 2.7), IAM (M = 17.3, SD = 3.60), and FIM scores (M = 17.3, SD = 3). The OTs also had high mean scores on self-perceived achievement of change objectives and intervention fidelity. Qualitative interviews suggested that the time commitment for Clinician Education is a key barrier to its acceptability, appropriateness, and feasibility. Participants also provided suggestions on how to improve the strategies (e.g., providing recorded Clinician Education, etc.). Conclusions The MyGoals implementation strategies are acceptable, appropriate, and feasible to OTs working in community-based rehabilitation. They support OTs in achieving the change objectives necessary to deliver MyGoals completely and competently. Thus, the MyGoals implementation strategies may support clinicians in implementing a theory-based, client-engaged goal setting and goal management for adults with chronic conditions in community-based rehabilitation. This can ultimately help improve the integration of evidence-based interventions into practice.